2023
DOI: 10.9734/ajpr/2023/v11i3220
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Masturbation-Treated with Anti-Epileptic Drugs: Experience of a Tertiary Care Pediatric Hospital in Bangladesh

Abstract: Aim: This study was aimed to find out the mismanagement of infantile masturbation and the outcome of the cases who were treated with anti-epileptic drugs. Study Design: Retrospective. Place and Duration of Study: This study was conducted at outpatient department of Rehabilitation and Neurology unit of Dr. M R Khan Shishu Hospital and Institute of Child Health, Dhaka Bangladesh, between 2013-2022. Methods: Data were collected from records which included socio-demographic data and clinical feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…In agreement with our findings, Unal observed that family type and economic level were statistically unimportant when comparing patients and controls [14] , which agrees with our findings. Rahman et al [23] discovered that the majority of patients (46% and 50%, respectively) belonged to the medium and upper income groups in their study. However, Dhaher et al [24] discovered that masturbatory behaviour was more widespread in lower socioeconomic classes (68%).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In agreement with our findings, Unal observed that family type and economic level were statistically unimportant when comparing patients and controls [14] , which agrees with our findings. Rahman et al [23] discovered that the majority of patients (46% and 50%, respectively) belonged to the medium and upper income groups in their study. However, Dhaher et al [24] discovered that masturbatory behaviour was more widespread in lower socioeconomic classes (68%).…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, Ajlouni et al [12] revealed that the typical number of incidents in their study was four per day, with a median length of 3.9 minutes. According to Rahaman et al [23] the majority of episodes (48%) lasted 3-5 minutes, subsequently followed by less than 3 minutes (28%) and happened 3-5 times per day (66%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations